Transitional justice and the problem of democratic decline - Dancy, Geoff (International journal of transitional justice, 2025)
When transitional justice emerged as a field of practice amid the third wave of democracy, many hoped it would reinforce the rules and norms that prevent democratic decline. However, over half of all the democracies that transitioned from autocracy or experienced civil war in the last half-century have since undergone backsliding or breakdown. Is transitional justice partly to blame? This article theorizes six ways that transitional justice might contribute to democratic decline, or alternatively, to democratic progress. It then analyzes data from 118 democratic spells in 89 countries spanning 1970 to 2023 to evaluate which hypotheses are plausible. In line with theories focused on endogenous change, the findings suggest that transitional justice is actually associated with stronger electoral and judicial institutions, which reinforces the guardrails of democracy against autocratic reversion. Yet, while transitional justice might help prevent full democratic breakdown, it does not hinder democratic backsliding, particularly that which is driven by government restrictions on civic association.